Kinerja Pengelola Perpustakaan Sekolah dalam Meningkatkan Minat Baca Siswa Kelas IV di SDN No.96/II Desa Ujung Tanjung Kecamatan Jujuhan Kabupaten Bungo - Azhar, Mhd (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2021)
This research is conducted to determine the standards of school library management in SDN No.96 / II Ujung Tanjung Village, Jujuhan Subdistrict, Bungo Regency. The method used in this study is qualitative descriptive with non-participant observation techniques, interviews, and communication as data collection techniques. The analysis technique uses data triangulation. The results showed that the performance of school library managers to increase the reading interest of grade IV students in SDN n0. 96/II UjungTanjung Village, Jujuha Subdistrict, Bungo Regency, namely (1) the management of the library has not met the standards of the national library; (2) the library's target has not been achieved; and (3) have not found the results/goals achieved.